1993
DOI: 10.1007/bf01973681
|View full text |Cite
|
Sign up to set email alerts
|

Surface binding and uptake of cadmium (Cd2+) by LLC-PK1 cells on permeable membrane supports

Abstract: Recent studies have shown that Cd2+ has relatively specific damaging effects on cell-cell junctions in the renal epithelial cell line, LLC-PK1. The objective of the present studies was to examine the surface binding and uptake of Cd2+ by LLC-PK1 cells in relation to the disruption of cell-cell junctions. LLC-PK1 cells on Falcon Cell Culture Inserts were exposed to CdCl2 containing trace amounts of 109Cd2+ from either the apical or the basolateral compartments, and the accumulation of 109Cd2+ was monitored for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…To differentiate between apical and basolateral chemokine secretion, we used cell culture inserts as basement membrane imitation. This model has been previously established for renal tubular epithelial cells [17, 18, 19]. Here we show that IL-8 as well as MCP-1 secretion by TEC after stimulation with IL-1α is preferentially directed to the basolateral environment.…”
Section: Discussionmentioning
confidence: 66%
“…To differentiate between apical and basolateral chemokine secretion, we used cell culture inserts as basement membrane imitation. This model has been previously established for renal tubular epithelial cells [17, 18, 19]. Here we show that IL-8 as well as MCP-1 secretion by TEC after stimulation with IL-1α is preferentially directed to the basolateral environment.…”
Section: Discussionmentioning
confidence: 66%
“…Such effects have been observed in vitro on filter-grown Caco-2 cells and found to be concentration-and time-dependent occurring at 5 lM Cd following a 4-h period of exposure (Duizer et al 1999). In LLC-PK1 cells, decrease in TEER has been found to be an early-response and more sensitive marker of Cd cytotoxicity than lactate dehydrogenase leakage or cell detachment (Prozialeck and Lamar 1993). Therefore, we tested whether Cd at the levels used in the present study may impair tight junctions, leading to Cd leakage through the paracellular pathways.…”
Section: Higher Bl Uptake Of CD In Differentiated Cells Exclusivelymentioning
confidence: 90%
“…No stimulation after exposure to differently fimbriated E. coli was seen (23). Other investigators described a polarity of renal tubular epithelium cultured on microporous cell culture inserts (26,30). Recently, Phillips et al reported that proximal tubular cells secrete transforming growth factor ␤ 1 equally into the apical and basolateral compartments only after basolateral exposure to platelet-derived growth factor in combination with D-glucose (25).…”
Section: Discussionmentioning
confidence: 99%